Eyeling Lymphoma in a Cat - Borges Vaz, Bruna; da Silva Flores, Fabiano; Dutra Corrêa, Luís Felipe (Acta Scientiae Veterinariae, 2025)
Background: Lymphomas represent approximately 80% of hematopoietic tumors in felines. This species can present neoplasia spontaneously or through viral oncogenic action, with FIV being able to play a direct oncogenic role, while FeLV has been the main viral agent involved. Combined lymphomas are predisposed in mixed breed felines between 1 and 15 years of age, where 37.5% are seropositive for FIV or FeLV and only 12.5% ​​for both. Diagnosis must include imaging tests, cytological and/or histopathological analysis of the compromised tissue. Staging and prognostic factors depend on the location of the tumor, whether it can be treated with isolated therapy, such as surgical interventions, or requires systemic therapies such as chemotherapy and/or radiotherapy. The objective is to report a case of eyelid lymphoma in a cat negative for FIV/FeLV, in stage IV, presenting a state of total eyelid remission after chemotherapy treatment and clinical stability during 6-month monitoring. Case: A 10-year-old spayed female mixed breed cat, weighing 3.8 kg, was attended with main complaint based on the failure to open the right eye, due to the presence of a nodule in the lower eyelid. With the presence of eyelid neoplasia in the right eye and due to the patient’s age, a chest x-ray and abdominal ultrasound were performed, showing gastrointestinal, hepatic and mesenteric lymph node changes. In view of the findings, a clinical suspicion of a multifocal oncological condition was raised, opting for an incisional biopsy of the eyelid nodule and forwarding it to a histopathological examination, in order to define the diagnosis. The result of the histopathological analysis was conclusive for lymphoma, requiring chemotherapy treatment for tumor remission, given that the patient was unable to open her eye and because it was a malignant neoplasm. After the 6th session, the patient was discharged, being monitored monthly, currently totaling 6 months of hematological follow-up within normal limits and without signs of tumor recurrence. Discussion: Extranodal sites where feline lymphoma frequently develops include the kidneys, spleen, tonsils, eyes, nasal region, and central nervous system. Neoplasms that cause ophthalmic discomfort can develop bulbar changes that are harmful to vision. With post-biopsy histopathological analysis, it was possible to classify the patient with combined lymphoma in stage IV, which must present a single extranodal tumor in an anatomical area, in this case eyelid neoplasia, associated with the presence of intestinal changes with or without implication of the mesenteric lymph nodes, in addition to involvement of the liver or spleen, corroborating the findings of complementary exams. Generally, the percentage of cats with lymphoma that enjoy a complete response to chemotherapy is between 50% and 70%, the average remission time is 4 months and the average survival time is 6 months. The association between vincristine and prednisolone obtained a satisfactory result in this case, as it met the objective of total remission of the eyelid neoplasia and provided stability in the systemic condition, with no recurrences of the extranodal nodule or signs of general clinical worsening. FIV/FeLV-negative felines can develop isolated or multifocal neoplastic processes, which, when present in the periocular region, must be diagnosed briefly and subjected to effective therapies, in order to avoid ophthalmic complications that worsen the patient’s clinical condition, as well as promoting quality. and life expectancy with total resolution and/or stability of the diagnosed changes. Keywords: lymphoma, eyelid neoplasm, feline, biopsy, chemotherapy. Título: Linfoma palpebral em uma gata Descritores: linfoma, neoplasia palpebral, felino, biópsia, quimioterapia.